2002
DOI: 10.5253/arde.v68.p225
|View full text |Cite
|
Sign up to set email alerts
|

The Prudent Parent: Energetic Adjustments in Avian Breeding1)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
1,194
9
19

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,293 publications
(1,266 citation statements)
references
References 85 publications
44
1,194
9
19
Order By: Relevance
“…Instead, males may adjust their reproductive effort facultatively, whereas a female commits herself to major investment whenever she "decides" to reproduce (although we doubt that most animals make conscious decisions). The capital versus income breeder dichotomy, where resources necessary for reproduction originate from body reserves versus from the food gathered at the time of reproduction (Drent and Daan, 1980;Stearns, 1992;Jö nsson, 1997), offers a conceptual framework for this result. Capital breeders are expected to invest in reproduction only after enough body reserves (the capital) have been accumulated to reach a "body-condition threshold" (sensus Stearns, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, males may adjust their reproductive effort facultatively, whereas a female commits herself to major investment whenever she "decides" to reproduce (although we doubt that most animals make conscious decisions). The capital versus income breeder dichotomy, where resources necessary for reproduction originate from body reserves versus from the food gathered at the time of reproduction (Drent and Daan, 1980;Stearns, 1992;Jö nsson, 1997), offers a conceptual framework for this result. Capital breeders are expected to invest in reproduction only after enough body reserves (the capital) have been accumulated to reach a "body-condition threshold" (sensus Stearns, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In others there appears to be no discernible relationship (e.g., if clutch and offspring sizes are fixed) or a complex nonlinear relationship between the two variables. For example, many organisms are "capital breeders" that rely on previously gathered energy stored in the form of body reserves (i.e., fat bodies, proteins) rather than on current energy intake to fuel the energetically costly process of reproduction (Drent and Daan, 1980;Jö nsson, 1997;Bonnet, Bradshaw, and Shine, 1998). In such species, life history theory predicts that a threshold level of energy reserves is necessary for a reproductive cycle to begin, rather than a linear relationship in which an increment in energy availability adds an increment in reproductive output (Schaffer, 1974;Bull and Shine, 1979;Stearns, 1992).…”
mentioning
confidence: 99%
“…It has been suggested that in order to initiate egg laying, birds must reach a body condition 181 threshold, and that individual host body condition necessarily delays or advances threshold 182 attainment (Drent & Daan, 1980). For example, parasites that undergo hepato-pulmonary migration 183 and/or cause anaemia via exsanguination compete with the host for protein during the time when 184 energy input is concentrated on egg production (Allander & Bennett, 1995).…”
Section: Effect Of S Trachea On Body Condition 137mentioning
confidence: 99%
“…Life-history theory predicts that to maximize its lifetime reproductive success, an individual will invest a specific amount in reproduction resulting from the trade-off between the benefits and costs associated with raising chicks (Stearns 1989). In this context, long-lived birds are expected to favor their survival at the expense of the current breeding attempt (Stearns 1989, Mauck andGrubb 1995, and see the ''prudent parent'' in Drent and Daan 1980), and should minimize risks when investing in their offspring (Goodman 1974). Parental investment, defined as ''any investment by the parent in an individual offspring that increases the offspring chances of surviving at the cost of the parent ability to invest in other offspring'' (Trivers 1972), includes features in birds such as nest building, egg incubation, chick rearing, nest defense, and foraging.…”
Section: Introductionmentioning
confidence: 99%